Investigation of new materials for fast speed phase-change random access memory - Law, Minghui (2009)
Phase Change Random Access Memory (PCRAM) has shown to have the most potential over other types of emerging non-volatile memories to become an alternative to FLASH memories. However, several problems regarding its practical use still remain. In this project, studies to increase the life time of the PCRAM through insertion of a diffusion barrier were performed. Germanium nitride (GeN) with 45.05 at% nitrogen had shown excellent properties as a diffusion barrier and had been incorporated into the PCRAM cell structure to investigate its device performance. GeN films with high nitrogen content showed excellent thermal stability, good RMS surface roughness and high electrical resistivity and these are important parameters for the PCRAM device.